IS ENGLISH ACADEMIC WRITING AS SIMPLE AS USING TRANSLATION TOOL? ERROR ANALYSIS ON STUDENTS' ABSTRACT - Naria Fitriani; Sabarniati Sabarniati; Nani Safuni (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2021)
Writing is not a spontaneous ability in language learning because it requires both editing and revising, and thus making this skill perceived as an easy task. Students could use a dictionary to help them use a foreign language on any occasion. Nonetheless, these activities may result in several errors in students' writing assignments. Relating to this situation, this study aims at identifying the students’ problems and their grammatical errors during the process of academic writing. In this study, mix-methods were applied in which vocational college students’ writings were documented and interview with the students was conducted. The data on students’ grammatical errors were collected, transcribed, analyzed, and interpreted. The findings show that the students’ errors laid on tense (38.0%), preposition (11.7%), article (11.4%), conjunction (11.4%), omission (8.9%), subject-verb agreement (6.3%) and adverb (2.5%). Meanwhile, based on the interview, to facilitate language competence, a translation tool such as Google translate was routinely used by most of the students (81.8%) during the writing completion. Although applying a translation tool in writing, the majority of the students (73%) thought it is a hard skill, and 18% of them believed that the writing process is the most difficult in language activities.